Overview of SEDEX Pb-Zn deposits - Suzanne Paradis (Canadian Institute of Mining, Metallurgy and Petroleum, 2006)
Geographic distribution ? Deposit economics ? Temporal distribution ? Tectonic settings ? Basin architecture ? Morphology ? Ore-fluid chemistries Key exploration criteria